Morphology of rat brain neurons in subtotal ischaemia and introduction of L-NAME and omega-3 polyunsaturated fatty acids - Bon, Lizaveta; Maksimovich, Natalia Ye.; Zimatkin, Sergey M. (Journal of Medical Science, 2020)
Introduction. Cerebral ischaemia leads to the development of numerous morphofunctional disorders of the cerebral cortex, which can be exacerbated by the introduction of a Nω-nitro-L-arginine methyl ester (L-NAME), which is a non-selective inhibitor of nitric oxide synthase (NOS). Aim. To study the morphological features of rat brain neurons in subtotal ischaemia during the administration of L-NAME and naturally occurring omega-3 polyunsaturated docosahexaenoic acid (DHA). Material and Methods. Subtotal cerebral ischaemia was modelled in rats by ligation of both common carotid arteries. L-NAME and DHA were given individually or in combination to separate groups of rats. L-NAME (5 mg/kg) was administered intramuscularly immediately before ligation and DHA (5 mg/kg) intragastrically during the week before ligation. Results. The introduction of DHA alone had a corrective effect on the hippocampus under conditions of subtotal ischaemia, reducing the number of shadow cells and hyperchromic wrinkled neurons, without significantly affecting the size and shape of the neurons of the parietal cortex. However, the previous administration of DHA to rats with cerebral ischaemia receiving a NOS inhibitor did not abrogate the negative effects on the state of the neurons in the cerebral cortex. Conclusion. The administration of DHA can modulate the morphological disorder of the hippocampus which occurs in subtotal cerebral ischaemia.